The perils and promises of democratization through United Nations transitional authority: lessons from Cambodia and East Timor - Croissant, Aurel (Democratization, 2008)
This article compares democratization under the aegis of the United Nations in Cambodia and East Timor. The analysis points to the inherent contradictions and problems of democratization in post-conflict situations and discusses the difficult issue of timing. It draws four generalized conclusions about democratization through international interim governments in post-conflict societies. First, UN-led interim governments can provide a solution to the problems of civil strife, insecurity, and political instability in disrupted states. Second, democratization through international interim governments in civil-war countries can be successful if the transitional authority is able to maintain a stable ‘hurting balance of power’ and to guarantee the parties' compliance with democratic procedures. Third, international interim regimes like UNTAC are designed on the premise that reconciliation among the domestic parties is possible. If the premise turns out to be inaccurate, the very foundation of the peace process is challenged and it will be almost impossible successfully to adjust the interim government's institutional structure. Fourth, the cases of Cambodia and East Timor demonstrate that democratization must be embedded in a comprehensive agenda of political, social, and economic methods of peace-building. If interim governments end before the roots of democracy are deep enough and before democratic institutions are strong enough to stand alone, then the entire endeavour may fail.